2018
DOI: 10.1159/000495778
|View full text |Cite
|
Sign up to set email alerts
|

Combined Phenotypes of Spondylometaphyseal Dysplasia-Kozlowski Type and Charcot-Marie-Tooth Disease Type 2C Secondary to a TRPV4 Pathogenic Variant

Abstract: TRPV4, a nonselective calcium permeable ion channel, is expressed broadly in many organs including bone and neurons. Pathogenic variants in TRPV4 are known to cause both a spectrum of skeletal dysplasias and neuropathies. Recent publications have documented a few patients who have a combined phenotype of skeletal dysplasia and neuropathy secondary to TRPV4 pathogenic variants. We present an additional patient who has an overlapping neuromuscular and skeletal phenotype secondary to a TRPV4 pathogenic variant. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
8
0
3
Order By: Relevance
“…Whereas some mutations cause autosomal dominant Charcot–Marie–Tooth disease type 2C and related forms of spinal muscular atrophy 1 3 , conditions characterized by variably severe motor axonal degeneration with resultant weakness of the upper and lower extremities, other distinct mutations cause unrelated diseases of bone and connective tissue, including various forms of skeletal dysplasia, inherited osteoarthropathy, and hereditary osteonecrosis 4 7 . There are only rare examples of patients manifesting combined phenotypes 8 10 . Thus, TRPV4 mutations cause a spectrum of human diseases affecting the nervous system, connective tissue, and bone, tissues that are linked by their requirement for a robust cytoskeleton that can adapt and respond to dynamic extracellular stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas some mutations cause autosomal dominant Charcot–Marie–Tooth disease type 2C and related forms of spinal muscular atrophy 1 3 , conditions characterized by variably severe motor axonal degeneration with resultant weakness of the upper and lower extremities, other distinct mutations cause unrelated diseases of bone and connective tissue, including various forms of skeletal dysplasia, inherited osteoarthropathy, and hereditary osteonecrosis 4 7 . There are only rare examples of patients manifesting combined phenotypes 8 10 . Thus, TRPV4 mutations cause a spectrum of human diseases affecting the nervous system, connective tissue, and bone, tissues that are linked by their requirement for a robust cytoskeleton that can adapt and respond to dynamic extracellular stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…However, we identified 36 individual cases of mixed neuropathy and skeletal phenotypes arising from 19 different mutations. 10,11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34] This included nine affected families as well as several individuals with de novo mutations. We analyzed these reports with respect to genotype, age of onset, neurological and skeletal manifestations, electrophysiology, and other phenotypic manifestations (Table 2).…”
Section: Literature Review Of Combined Phenotypesmentioning
confidence: 99%
“…Although disease progression was not uniformly assessed, there was evidence of disease progression in 21 out of 23 patients (91%) for which longitudinal information was reported. Progression was evidenced by development of muscle atrophy, 25 worsening weakness, 25 gait impairment, 26 sensory deficits, 28 and/or was demonstrated with electrodiagnostic studies. 10,11 When reported, electrophysiological studies showed motor greater than sensory axonal neuropathy and evidence of denervation potentials on needle EMG.…”
Section: Literature Review Of Combined Phenotypesmentioning
confidence: 99%
“…Therefore, the strategy of inhibiting TRPV4 has been demonstrated to possess neuroprotective effects in treating cerebral ischemic injuries in both in vitro and in vivo experiments [ 86 , 133 ]. Currently, many diseases are associated with TRPV4 mutations in humans, which are mainly related to various abnormal neurologic and/or musculoskeletal symptoms, including Charcot–Marie–Tooth disease type 2C [ 134 ], scapuloperoneal spinal muscular atrophy [ 135 ], congenital distaspinal muscular atrophies [ 136 ], autosomal dominant brachyolmia [ 137 ], and spondylometaphyseal dysplasia Kozlowski type [ 138 ]. Trpv4 KO mice results demonstrated a possible role of Trpv4 inhibition in preserving microcirculation and BBB/GVU function in mice bearing MCAO surgery [ 139 ].…”
Section: Functions Of Trpv1–4 In Modulating Bbb Under Healthy and mentioning
confidence: 99%